Intra-ocular pressure changes after intravitreal injection of bevacizumab - Iqbal, Usama; Qayyum Malik, Irfan; Jabran, Aamna (Journal of the Pakistan Medical Association, 2022)
Objectives: To evaluate the short-term and sustained intraocular pressure changes after intravitreal bevacizumab in patients with diabetic retinopathy. Method: The quasi-experimental study was conducted at the District Headquarter Teaching Hospital, Gujranwala, Pakistan, from January to December 2020, and comprised diabetic patients of either gender aged 18-60 years with indication for intravitreal bevacizumab. Intraocular pressure was measured at 5, 10 and 30 minutes for short-term elevation, and the patients were followed up weekly for one month to record any sustained elevation in intraocular pressure. Data was analysed using SPSS 25. Results: Of the 42 patients, 20(47.61%) were male and 22(52.38%) were female. The overall mean age was 52.4±5.7 years. Intraocular pressure increased significantly in the short term post-injection (p<0.001), while the difference was not significant in the weekly check-ups (p=0.264). Conclusion: There was short-term rise in intraocular pressure after intravitreal bevacizumab, but no sustained elevation was noted over the following month. Key Words: Vascular endothelial growth factor, Bevacizumab, Intraocular pressure, Diabetic retinopathy.